Determination of Meropenem and Ertapenem in Lagoon Water, Bedding Soil, and Silage by High-Performance Liquid Chromatography–Tandem Mass Spectrometry. (13th June 2017) - Liu, Yuan; Liu, Jianye; Li, Xiaowei; Zhao, Kunxia; Zhang, Pengchun; Ding, Shuangyang
ABSTRACT: A simple and sensitive method was developed and validated by high-performance liquid chromatography–tandem mass spectrometry (HPLC–MS/MS) for the determination of meropenem and ertapenem in environmental materials from dairy farms. The limits of quantification were between 1 and 20 ng/mL for the analytes in lagoon water, bedding soil, and silage. The recoveries for meropenem and ertapenem exceeded 80%. The intraday and interday precision values were less than 15% in all samples. The validated method was employed to determine the meropenem and ertapenem in environment samples obtained from dairy farms.